Colon cancer as content of an inguinal hernia - Palacio, José Luis; Cluzet, Oscar; Font, Francisco; Müller, Augusto; El-Ters, Antuán (Cirugía del Uruguay, 1993)
A case of colonic cancer as content of inguinal hernia is presented. This is a rare lesoinal association. The studies that made preoperative diagnosis possible are analysed and a bibliographical revision is made.